Constituti ng the punishable woman. Atavistic man incarcerates postmodern woman - Snider, Laureen (The British journal of criminology, 2003)
This paper reviews feminist and non-feminist knowledge claims on the punishment of women from 1970 to 2000, linking the incarceration spiral to conceptual, ideological, economic and political shifts in western societies overall. It argues, first, that the knowledge claims of critical criminology - a designation that includes feminist criminology - are components of the incarceration spiral, and that this factor must be fed back into analyses of the knowledge/power equation. The paper examines how constructions of women developed by claims makers in feminist criminology have structured the ways in which women are now punished. Second, this means that the claims of all the variants of criminology, from right realist to critical and postmodern, are complicit in the surge of punitiveness that characterizes the modern industrialized state. However, to understand the woman of punishable discourse constituted through criminal law today, one must look beyond academe and ask not what discourses are produced, but what discourses are heard, by politicians, the public, and criminal justice professionals. This shifts the analytical focus from deconstruction to political economy